Homomeric and native α7 acetylcholine receptors exhibit remarkably similar but non‐identical pharmacological properties, suggesting that the native receptor is a heteromeric protein complex - René Anand; Xiao-ding Peng; Jon Lindstrom (1993)
Sucrose gradient analysis of chick acetylcholine receptor (AChR) α7 subunits expressed in oocytes indicates that they form pharmacologically active homomers of the same size as native α7 AChRs, a size compatible with a complex of five α7 subunits. By immunoisolating the [ 35 S]methionine‐labeled α7 subunits we also demonstrate that they do not appear to assemble with endogenous Xenopus AChR subunits. Pharmacological characterization of detergent‐solubilized brain α7 AChRs and α7 homomers reveals that they have similar but nonidentical properties. The pharmacological difference is most accentuated for cytisine (~50‐fold). Thus, at least in E18 chicken brain, most or all of the native α7 AChRs do not appear to be homomeric.